2015
DOI: 10.1111/liv.12756
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of TLRIFN and HLA polymorphisms on susceptibility of chronic HBV infection in Southwest Han Chinese

Abstract: Background & Aims: The toll-like receptor-interferon (TLR-IFN) signalling pathway plays a crucial role in HBV infection. Human leucocyte antigen (HLA) polymorphisms are associated with chronic HBV infection by genome wide association study (GWAS). We aimed to explore interaction between TLR-IFN and HLA gene polymorphisms in susceptibility of chronic HBV infection. Methods: In the Chinese Southwest Han population, 1191 chronic HBV infection patients and 273 HBV clearance were selected. A total of 39 single nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Conversely, two common SNPs in the TLR9 gene (promoter flanking rs187084 and rs352140 in the second exon) which showed significance for both allele and genotype frequencies (p < 0.05) in our analysis (Table II) did not reach the level of significance in an earlier association study on the risk of invasive aspergillosis among recipients of allogeneic haematopoietic cell transplants [19]. Nevertheless, many other studies have proved associations of rs187084 and rs352140 with numerous immune-related diseases, response to therapies, as well as bacterial and viral infections in populations of both Western and Eastern Eurasian ancestry [20,21,22,23,24,25]. It is also worth noting that the common rs4586 SNP, flanking the promoter of CCL2 gene, which appeared significant for genotype frequencies between our cases and controls (p = 0.0079, OR = 8.5, Table II), was recently found to be significantly correlated with anti-tumour immune reaction in Korean patients with colorectal cancer [26] and associated with the clinical outcome in Japanese individuals with locoregional gastric cancer [27].…”
Section: Resultsmentioning
confidence: 40%
“…Conversely, two common SNPs in the TLR9 gene (promoter flanking rs187084 and rs352140 in the second exon) which showed significance for both allele and genotype frequencies (p < 0.05) in our analysis (Table II) did not reach the level of significance in an earlier association study on the risk of invasive aspergillosis among recipients of allogeneic haematopoietic cell transplants [19]. Nevertheless, many other studies have proved associations of rs187084 and rs352140 with numerous immune-related diseases, response to therapies, as well as bacterial and viral infections in populations of both Western and Eastern Eurasian ancestry [20,21,22,23,24,25]. It is also worth noting that the common rs4586 SNP, flanking the promoter of CCL2 gene, which appeared significant for genotype frequencies between our cases and controls (p = 0.0079, OR = 8.5, Table II), was recently found to be significantly correlated with anti-tumour immune reaction in Korean patients with colorectal cancer [26] and associated with the clinical outcome in Japanese individuals with locoregional gastric cancer [27].…”
Section: Resultsmentioning
confidence: 40%
“…Several studies, especially analyzing Asian samples, found association between the SNP rs9277535 and chronic HBV infection (Kamatani et al, 2009;Lau et al, 2011;Mbarek et al, 2011;Png et al, 2011;Nishida et al, 2012;Yan et al, 2012;Kim et al, 2013;Al-Qahtani et al, 2014;Chang et al, 2014;Liao et al, 2014;Pan et al, 2014;He et al, 2015;Yu et al, 2015). Additionally, the study conducted by Thomas et al (2012) found an association between the SNP rs9277535 and the elimination rate of HBV in patients EuroAmerican and African-Americans (P = 0.0001).…”
Section: Discussionmentioning
confidence: 97%
“…In the study conducted by O'Brien et al (2011), the SNP rs9277535 was associated with a reduction in HLA-DPB1 gene expression in European patients. In Asian studies, the SNP rs7453920 was associated with the immune response to HBV (Mbarek et al, 2011;Al-Qahtani et al, 2014;Liao et al, 2014;He et al, 2015). However, no studies have associated this SNP in samples from other regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some discrepancies as some studies did not find any genetic association of rs16944 with IL‐1β levels , infection or sepsis . In non‐European population, the rs16944 AA genotype has been related to lower risk of infection , and the GG genotype was associated with production of IL‐1β and higher risk of infection . Additionally, we performed an in silico analysis for evaluating the possible functional implication of rs16944 polymorphism using rSNABase (http://rsnp.psych.ac.cn/) .…”
Section: Discussionmentioning
confidence: 99%